2003
DOI: 10.1046/j.1523-1755.63.s83.8.x
|View full text |Cite
|
Sign up to set email alerts
|

A stereological study of glomerular number and volume: Preliminary findings in a multiracial study of kidneys at autopsy

Abstract: These extraordinary ranges of glomerular number and size among ostensibly "normal" people, and their inverse relationship, probably have important implications for susceptibility to renal insufficiency. People with low glomerular (nephron) numbers are likely to be particularly predisposed, with the process marked by compensatory hypertrophy of residual nephrons, which, in turn, accelerates their obsolescence. Much, however, remains to be done, including evaluation of history, clinical features, accompanying pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

16
247
1
5

Year Published

2004
2004
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 323 publications
(269 citation statements)
references
References 13 publications
16
247
1
5
Order By: Relevance
“…In humans, it has been suggested that sudden infant death syndrome is associated with lower birth weights (22) and lower nephron numbers (23), although later studies do not confirm this (24). The range of nephrons found in our control fetuses was large, as in the human population (25). Given the strong link between birth weight and nephron number in many studies, the wide range in the control animals is probably due to the spectrum in birth weights observed in a normal population (26).…”
Section: Discussionmentioning
confidence: 73%
“…In humans, it has been suggested that sudden infant death syndrome is associated with lower birth weights (22) and lower nephron numbers (23), although later studies do not confirm this (24). The range of nephrons found in our control fetuses was large, as in the human population (25). Given the strong link between birth weight and nephron number in many studies, the wide range in the control animals is probably due to the spectrum in birth weights observed in a normal population (26).…”
Section: Discussionmentioning
confidence: 73%
“…There is substantial variation in nephron endowment across the population (22). A low nephron endowment is associated with larger glomeruli, low birth weight (23,24), and increased risk of kidney failure (25,26).…”
Section: Discussionmentioning
confidence: 99%
“…[48][49][50] The reason for the unaltered kidney volume in the elderly despite age-related glomerulosclerosis 51 may be the compensatory hypertrophy of unaffected nephrons in response to the significant nephron loss caused by glomerulosclerosis and tubular atrophy. 4 Studies have reported both increased volume in the functional glomeruli and decreased glomerular density in aging kidneys. [52][53][54][55] The pathological characteristics of aging kidneys include glomerular sclerosis, tubular atrophy and tubulointerstitial fibrosis.…”
Section: Pathological Changes In Aged Kidneysmentioning
confidence: 99%
“…2 Renal mass decreases between the ages of 30 and 80 years, with the steepest decline observed after age 50. 3,4 Fat and fibrosis scarring may replace some of the remaining functional parenchymal tissue. [4][5][6] This scarring and loss of kidney parenchymal tissue occurs primarily in the renal cortex; 6 therefore, scarring affects the nephrons that are important for maximal urine concentration.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation